2023
DOI: 10.1007/s10639-023-11688-7
|View full text |Cite
|
Sign up to set email alerts
|

Technology integration in emergency remote teaching: teachers’ self-efficacy and sense of success

Abstract: Sense of success and self-efficacy regarding technology integration in teaching are among the most important factors that influence teachers' well-being and professional development, and may have a substantial impact on student learning. In this quantitative study (N = 735 K-12 teachers in Israel), we explored the factors contributing to sense of success in emergency remote teaching and self-efficacy for integrating technology in teaching following the experience of teaching during COVID-19 days. We use decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 127 publications
0
1
0
Order By: Relevance
“…In another work, the authors of [32] reports a quantitative study of 735 K-12 teachers in Israel, exploring the factors that contribute to their sense of success and self-efficacy for integrating technology in ERT. The research uses decision-tree models to reveal the influence of experience, emotional difficulties, leadership roles, and subject domains on teachers' outcomes.…”
Section: Role Of Technological Infrastructure In Ertmentioning
confidence: 99%
“…In another work, the authors of [32] reports a quantitative study of 735 K-12 teachers in Israel, exploring the factors that contribute to their sense of success and self-efficacy for integrating technology in ERT. The research uses decision-tree models to reveal the influence of experience, emotional difficulties, leadership roles, and subject domains on teachers' outcomes.…”
Section: Role Of Technological Infrastructure In Ertmentioning
confidence: 99%
“…Studies have shown that the competence of teachers in the field of information technology is a key factor in the effective use of ICT in the classroom [42,43]. Hershkovitz [44] explored the factors contributing to a sense of success and self-efficacy in integrating technology in teaching following the experience of teaching during COVID-19. Afari et al [45] measured the association between the ICT self-efficacy of teachers and pre-service teachers' intentions to use technology.…”
Section: Teachers' Self-efficacy In Using Ict In Educationmentioning
confidence: 99%
“…As such, the integration of digital technologies into schools and academia required the development of a new pedagogy in teacher education (Koehler and Mishra, 2008), which then could be adapted to suit the various content disciplines (Cui and Zhang, 2021). Recently, this need for a unique pedagogy became even more urgent, as the world coped with the transition to digital teaching due to the COVID-19 pandemic (Ching and Roberts, 2020;Frei-Landau et al, 2022a;Muchnick-Rozanov et al, 2022b;Hershkovitz et al, 2023). Although digital learning and neuroeducation have been explored separately, the use of digital educational neuroscience-particularly in the context of special education-has yet to be addressed.…”
Section: Introductionmentioning
confidence: 99%